FORMULASI BOLU SEBAGAI MAKANAN PENDAMPING ASI (MP-ASI) SUBSTITUSI TEPUNG TEMPE DAN TEPUNG BAYAM MERAH - Oktavina Permatasari; Natalia Ratna Yulianti; Ariani Damayanti; Maria Dolorosa (Journal of Food Technology and Agroindustry, 2022)
The nutritional needs in the first 1000 days of life will affect the quality of health during their lifetime. Infants aged 6-24 months need complementary feeding to complement breast milk in an effort to fulfill their nutrition. Tempe flour is used as a source of protein and red spinach flour is used as a source of vitamins, minerals, and antioxidants needed by toddlers. The purpose of this study was to obtain the right formulation and preferred by panelists in the manufacture of complementary feeding sponge cake with the substitution of tempeh flour and red spinach flour. This research used one factor, sponge cake formulation as complementary feeding with four formulations using SPSS as well as organoleptic or sensory testing of SNI 01-2346-2006 with the object being studied a sponge cake, the treatment carried out in this study was the difference in the composition of the raw materials used and tested the characteristics of sponge cake as complementary feeding. Based on the results of the organoleptic test analysis, it was found that the sponge cake with the F2 formulation was the most preferred cake in terms of taste, color, and texture by 30 semi-trained panelists.